Prediction of Tacrolimus Drug Dosing and Metabolism based on CYP3A5 Polymorphism in Indian Renal Transplant Recipients. (July 2018) - Patel, Mohan; Goswami, Jitendra; Balwani, Manish; Gumber, Manoj
Abstract : Introduction: Tacrolimus (Tac) is mainstay of immunosuppressive regime in renal transplantation. However, it needs regular drug level monitoring in view of narrow therapeutic window. There is no study regarding systematic analysis of dose requirement of Calcineurin Inhibitor (CNI) in Indian patients. In our experience, dose of CNI to maintain TDL is significantly less compared to standard recommended dose of 0.1 mg/kg/day. So personalization of immunosuppressive therapy according to genetic profile may optimize drug dosing. Hence we conducted this study to assess impact of CYP3A5 polymorphism on dose requirements and metabolism of tacrolimus in renal transplant patients. Methods: This prospective observational study includes patients of end stage renal disease who underwent renal transplantion at our hospital during January 2012 to August 2014. Patients having at least 3 years follow-up were included for analysis. The starting dose of Tac was 0.08 mg/kg/day. Polymerase chain reaction, followed by restriction fragment length polymorphism analysis was used for genotyping CYP3A5*3 gene in intron 3 Results: Out of 50 patients included in the study, 36 had live related renal transplantation and 14 had diseased donor renal transplantation. Out of 50 patients (37 males and 13 females) who had polymorphism analysis for the CYP3A5, 40 patients have CYP3A5 homozygous status (A3986G polymorphism in CYP3A5*3 gene-wild allele) and 10 have heterozygous status. Patients of CYP3A5 homozygous status have mean Tac level of 16.84 ng/dL (range- 13.2-25 ng/dL) on 7th day of transplant. So Tac dose was reduced to achieve TDL and mean Tac level at 30th day of transplant was 6.6 ng/dL. At 6th, 12th and 3rd year of transplant, mean Tac levels were 6 ng/dL, 5.7 ng/dL and 3.7 ng/dL. Patients having CYP3A5 homozygous status, mean and median Tac dose after 4 weeks was 0.03 mg/kg/day (range- 0.008 to 0.05 mg/kg/day) and mean creatinine was 1.14 mg/dL (range-0.8 to 1.4 mg/dL) after 30th day. Remaining 10 patients having CYP3A5 heterozygous status were maintaining TDL at Tac dose of 0.07 mg/kg/day. Nine patients had graft biopsy during first 4 weeks of renal transplant showing acute tubular necrosis (ATN) in six patients, acute cellular rejection in one patient and cellular rejection with evidence of calcineurine inhibitor (CNI) toxicity in two patients. ATN observed was related to CNI toxicity as pre-renal and other etiologies were ruled out. Future large scale studies will demonstrate epidemiological status of CYP3A5 SNP in Indian patients and help to optimize drug dosing as per genetic status of the individual. Conclusion: Our results confirm that CYP35 genetic polymorphism is an important factor which influences Tac pharmacokinetics significantly with very low dose requirement. It should be done preoperatively to avoid CNI toxicity and related graft dysfunction in post-transplant period. Hence a pre-emptive CYP3A5 genotype analysis helps in better individualization of Tac therapy.